Postpartum Blood Loss in Women Treated for Intrahepatic Cholestasis of Pregnancy. Issue 5 (November 2016) - Furrer, Romana; Winter, Katharina; Schäffer, Leonhard; Zimmermann, Roland; Burkhardt, Tilo; Haslinger, Christian
Abstract : OBJECTIVE: To evaluate postpartum blood loss in women with treated intrahepatic cholestasis of pregnancy. METHODS: In a retrospective case–control study, 15, 083 deliveries including 348 women with intrahepatic cholestasis of pregnancy (2.3%) were analyzed from 2004 to 2014. To adjust for differences in baseline characteristics, a propensity analysis was performed and women in the control group were matched to the women in the intrahepatic cholestasis of pregnancy group in a 5:1 ratio. Blood loss was analyzed by estimated blood loss and Δ hemoglobin (Hb, difference between prepartum and postpartum Hb). A subgroup analysis regarding severity of intrahepatic cholestasis of pregnancy based on maximum bile acid level (mild [less than 40 micromoles/L], moderate [40–99 micromoles/L], and severe intrahepatic cholestasis of pregnancy [100 micromoles/L or greater]) was performed. Differences in estimated blood loss, ΔHb, and meconium staining between subgroups were analyzed. A Spearman rank correlation was performed to evaluate the association of bile acid levels and blood loss within subgroups. RESULTS: Estimated blood loss (median 400 [300–600] mL compared with 400 [300–600] mL, P =.22), ΔHb (14.0 [5.0–22.0] compared with 12.0 [4.0–21.0] g/L, P =.09), meconium staining (14.5% compared with 11.4%, P =.12), and number of stillbirths after 26 weeks of gestation (0.6% compared with 1.8%, P =.10) were not significantly different in the study compared with the control group. In moderate and severe intrahepatic cholestasis of pregnancy, meconium staining was observed significantly more often compared with that in a control group (23.0% and 32.3% compared with 11.4%, P <.01). There was no correlation between estimated blood loss or ΔHb and severity of intrahepatic cholestasis of pregnancy. CONCLUSIONS: In our cohort of women with intrahepatic cholestasis of pregnancy who are treated with ursodeoxycholic acid and have planned delivery (induction of labor or planned cesarean delivery) at 38 weeks of gestation, no differences in postpartum blood loss were seen. Abstract : Postpartum blood loss is not increased in women treated for intrahepatic cholestasis of pregnancy.